PEMODELAN MATEMATIKA PREMI TUNGGAL BERSIH ASURANSI UNIT LINK SYARIAH - Supriadi, Nanang (Al-Jabar: Jurnal Pendidikan Matematika, 2017)
The exact risk factor can be managed by transferring the risk to the other party (in this case the insurance company). In this paper will be discussed more life insurance, as the development now there are types of insurance combined with investment, which is popular with the term Unit Link insurance. Unit link Syariah began to be launched as one of the fulfilment of the high needs of the community, the privilege of the product Unit of Islamic links is actually located in the elements of the laws in accordance with Islamic Syariah. The issues that will be discussed are how to get a single premium model of life insurance unit link Syariah with life insurance and investment fund allocation invested in investment product with a big interest rate of risk (financial approach) and investment product with the value of return maximum (actuarial approach). The resulting model is then implemented in case of examples by comparing the two approaches to see the shortcomings and advantages of Unit link lifetime life insurance when compared to life insurance. The result obtained from this research is the benefit obtained from Unit-linked sharia insurance on average will be greater if compared with life insurance for life, maximum benefit will be obtained Insurance Unit Link of sharia using actuarial approach compared to financial, but benefit with a relative financial approach more stable than actuarial approaches that tend to fluctuate.